Narratives of Narcolepsy in Everyday Life: Exploring Intricacies of Identity, Sleepiness, and Place - Eugene, Nicole (Lexington Books, 2023)
Numerous movies, YouTube videos, books, and public service announcements have begun to address people with narcolepsy, and this discourse has led to greater visibility and understanding about an often-misunderstood condition. In Narratives of Narcolepsy in Everyday Life: Exploring Intricacies of Identity, Sleepiness, and Place, Nicole Eugene draws on in-depth interviews, participant observation, and field notes to examine life with narcolepsy, witha particular focus on how certain socially-defined places play significant roles in determining the meaning of sleepiness, medication side effects, and other narcolepsy symptoms. Eugene also includes one autoethnographic essay that explores her own experiences with narcolepsy as a Black woman, refracted through the lens of the various places where sleepiness may arise. Throughout the book, an emphasis on making sense of narcolepsy by communicating with others with the condition demonstrates a peer-based approach to researching health communication and disabilities. Drawing on feminist disability studies, health communication, narrative inquiry, and autoethnography, this book is an example of interpretive qualitative communication research that renders the lives of vulnerable people with compassion and understanding.